Nutritional risk status and related influencing factors in patients with tuberculosis complicated with type 2 diabetes mellitus - Cao, Jing; Xie, Hebin; Yu, Zikai; Zhao, Sue (Frontiers in Nutrition, 2026)
ObjectiveTo investigate the nutritional risk status of patients with tuberculosis complicated with type 2 diabetes mellitus (TB-T2DM) and analyze the related influencing factors.MethodsA retrospective study was conducted on adult patients (aged ≥18 years) with tuberculosis complicated with type 2 diabetes mellitus who were hospitalized in the Tuberculosis Department of Changsha Central Hospital from January to December 2024. A total of 196 patients were included in this study. The general demographic characteristics, nutritional indicators, immune indicators, clinical-related indicators of the research subjects, as well as the scores of Nutritional Risk Screening 2002 (NRS-2002) were collected. To analyze the nutritional risk status of patients with different types of tuberculosis, and a multivariate logistic regression model was used to analyze the influencing factors of nutritional risk.ResultsAmong the 196 patients, 46.43% were found to have nutritional risk. When categorized by tuberculosis diagnosis type, among the 179 patients with pulmonary tuberculosis combined with type 2 diabetes mellitus (PTB-T2DM), 48.60% had nutritional risk, while among the 17 patients with extrapulmonary tuberculosis combined with type 2 diabetes mellitus (EPTB-T2DM), 23.53% had nutritional risk. Multivariate logistic regression analysis showed that albumin, neutrophil to lymphocyte ratio, glycated hemoglobin, and body mass index (24.0–27.9 kg/m2) were independent influencing factors for TB-T2DM.ConclusionPatients with TB-T2DM have a relatively high proportion of nutritional risk. Both nutritional and immune indicators have an impact on the occurrence of nutritional risk. In the clinical treatment process, more attention should be paid to the nutritional status of patients in order to reduce recurrence and improve prognosis.